THE IMPACT OF E-AUDIT ADOPTION AND AUDITOR COMPETENCE ON AUDIT QUALITY: EVIDENCE FROM PUBLIC ACCOUNTING FIRMS IN PADANG, INDONESIA - Putri Nabila Sundari; Teguh Hidayat; Dewi Zulvia; Elvirha Dwi Kartika (Jurnal Akuntansi Syariah (JAkSya), 2026)
The rapid development of information technology has brought significant changes to auditing practices, particularly through the implementation of e-audit in the financial statement examination process. The use of technology in auditing is expected to improve the effectiveness, efficiency, and quality of audit results. However, in practice, issues related to audit quality are still found, one of which is reflected in the suspension of the license of Anderson and Rekan Public Accounting Firm (KAP) by the Financial Services Authority in 2024 due to violations of auditing standards. This phenomenon indicates that audit quality remains an important concern influenced by various factors, including the use of audit technology and auditor competence. Therefore, this study aims to analyze the effect of e-audit implementation and auditor competence on audit quality at Public Accounting Firms (KAP) in Padang City. This study employed a quantitative method with a multiple linear regression analysis approach. The population in this study consisted of 71 auditors working at Public Accounting Firms (KAP) in Padang City. The research data were collected through questionnaires distributed to auditors working at Public Accounting Firms in Padang City using a purposive sampling technique, resulting in a sample of 40 auditors. The results showed that the implementation of e-audit had a positive and significant effect on audit quality, indicating that the utilization of audit technology is capable of improving the effectiveness and efficiency of the audit process, thereby producing better audit quality. Meanwhile, auditor competence had a positive but insignificant effect on audit quality. This study contributes theoretically by enriching the literature regarding factors affecting audit quality, particularly related to the implementation of e-audit and auditor competence. Practically, this study is expected to serve as a reference for Public Accounting Firms in improving audit quality through the utilization of audit technology and the continuous development of auditor competence.